Entity regulation, litigation rights and the changing meaning of professionalism at the Bar of England and Wales. (2nd July 2020) - Mason, Marc
ABSTRACT: The Legal Services Act 2007 provided a framework for a liberalised marketplace for legal services. The most significant responses to this by the Bar appear in the Bar Standards Board Handbook, which was first released in January 2014. This included changes allowing for barristers to engage in litigation and enabling the Bar Standards Board to regulate entities rather than just individual barristers. This article places these changes within the existing theoretical understanding of the legal professions and professionalism, and argues that they open the door for a significant shift in the way that the discourse of professionalism is used in relation to the Bar.